Browning's experiments with genre - Hair, Donald S. (Studies and texts (University of Toronto. Department of English), 1972)
This book explores the kinds and modes with which Browning worked and describes the nature of the experiments he made, concentrating on the earlier poetry and in particular on The Ring and the Book.